Advancing a Human Onchocerciasis Vaccine From Antigen Discovery to Efficacy Studies Against Natural Infection of Cattle With Onchocerca ochengi - Zhan, Bin; Bottazzi, Maria Elena; Hotez, Peter J.; Lustigman, Sara (Frontiers in Cellular and Infection Microbiology, 2022)
Human onchocerciasis is a devastating neglected tropical disease caused by infection of the filarial nematode Onchocerca volvulus. The infection can cause irreversible visual impairment or blindness and stigmatizing dermatitis. More than 32 million people were estimated to be infected with O. volvulus in Africa and 385,000 were suffered with blindness. Even though the implementation of mass drug administration (MDA) with ivermectin has reduced the global prevalence of onchocerciasis, O. volvulus infection remains challenging to control because MDA with ivermectin cannot be implemented in endemic areas co-endemic with loiasis due to the risk of severe adverse events. There is also emerging drug resistance to ivermectin that further complicates the elimination of onchocerciasis. Thus, the development of a vaccine that would induce protective immunity and reduce infection burden is essential. The efforts to develop prophylactic and/or therapeutic vaccines for onchocerciasis have been explored since late 1980s by many researchers and entities and here we summarize the recent advances made in the development of vaccines against the infection of O. volvulus and onchocerciasis.